Vietnamese young consumers’ green purchase behavior: Does green trust matter? - Son, Doan Bao; Phuc, Nguyen Huy; Kieu Anh, Nguyen Ngoc; Loc, Nguyen Dinh; Nghi, Tong Tinh; Hien, Pham Thi Thu (Tạp chí Nghiên cứu Tài chính - Marketing, 2024)
It is crucial to practice environmentally responsible purchasing since impulsive purchases can damage the environment. Green purchase behavior (GP) can help consumers lessen their environmental impact. An integrated structural model of GP was developed by drawing on postulates from the Protection Motivation Theory (PMT). A total of 302 Vietnamese university students were surveyed using the snowball sampling method. It was found through structural equation modeling (SEM) that there is a significant association between perceived severity (PS), perceived vulnerability (PV), and GP. The relationship between PS, PV, and GP is mediated by attitude toward green purchase (ATT). Also, green trust (GTR) plays a significant moderating role in the PV and GP relationship. The findings, including the correlations between the variables, provide credence to the suggested theoretical framework. Since studies on environmental problems and green purchasing behavior are still in their early stages, this work helps fill a gap in our understanding of the phenomenon in the context of Vietnam, a developing Southeast Asian economy. This research may help manufacturers and marketers of green products encourage the use of their products to improve environmentally friendly and sustainable behavior. The findings suggest marketers and manufacturers should emphasize environmental pollution’s perceived severity and vulnerability. It is also critical to establish consumers’ trust in green marketing.